Supported ionic liquids to purify microbial L-Asparaginase - Almeida, Mafalda R. (2024)
L-Asparaginase (ASNase) is a versatile enzyme that converts L-asparagine into ammonia and aspartic acid. This enzyme has applications in the food industry and health sector. However, high purity ASNase is required, resulting in high production costs. Therefore, in this work, two supported ionic liquids (SILs), specifically silica modified with dimethylbutylpropylammonium chloride ([Si][N3114]Cl) or triethylpropylammonium chloride ([Si][N3222]Cl), were investigated as alternative adsorption materials to purify ASNase. Different conditions were evaluated to improve enzyme purity, including total protein content in the cell extract, contact time, and SIL/cell extract ratio (w/v). Under optimal conditions using [Si][N3114]Cl, a maximum ASNase purification of 6.1-fold is achieved in a single step, resulting from the preferential attachment of other proteins on [Si][N3114]Cl SIL. According to the results, hydrophobic interactions rule the selective adsorption of protein impurities from the cell extract by the SIL, thereby increasing the ASNase purification levels. This approach offers a significant advantage, not requiring the desorption and elution of the target enzyme, while envisioning the application of SILs in a flow-through elution approach. The protonation state of protein surface was calculated by computational analysis, revealing that positively charged amino acids such as arginine and lysine block the effective binding of the enzyme to the SILs. Overall, if properly designed, SILs are promising alternative supports for the downstream processing of ASNase from cell extracts.